Local knowledge about sustainable harvesting and availability of wild medicinal plant species in Lemnos island, Greece - Dimitrios Papageorgiou; Penelope J. Bebeli; Maria Panitsa; Christoph Schunko (BMC, 2020)
Abstract Background In Europe and the Mediterranean, over-exploitation and destructive harvesting techniques have been identified as two critical threats affecting the sustainable harvesting of wild medicinal plant (WMP) species. However, unsustainable harvesting is not an issue everywhere and localized assessments are needed. Local knowledge has been praised for its potential for local short-term assessments. In this study, we aimed to register the known, harvested, and locally utilized WMP species and understand local knowledge of harvesters about the ecological sustainability of WMP harvesting and the perceived changes of WMP availability. Materials and methods This study was conducted on Lemnos island, Greece, in July and August 2018. Sixteen harvesters knowledgeable about gathering and using WMP were chosen through purposeful and snowball sampling. Successive free-lists provided insights on the taxa known, harvested, and utilized by harvesters and subsequent semi-structured interviews served to understand harvesting practices and perceived changes of WMP availability. Participant observation during seven harvesting walks allowed for additional insights and facilitated the collection of voucher specimens. Results In total, 144 different plant taxa were listed as useful and 81 had been harvested in the prior 4 years. Medicinal applications were mainly related to digestive and respiratory system issues. A number of favorable harvesting practices suggested a high potential towards an ecologically sustainable harvest. Although, a decreased availability for certain plant taxa and harvesting sites was reported and mainly attributed to external factors such as pollution, unusually dry weather, intentional pastureland burning or chemicals in agriculture, but also destructive harvesting by less knowledgeable harvesters. Conclusions Knowledgeable harvesters of Lemnos gather and use a considerable number of WMP taxa and possess local knowledge that supports an ecologically sustainable harvest. However, certain plant taxa and areas of the island were indicated to be under pressure from harvesting, unusual climatic conditions, and agricultural practices. Our approach confirmed that local knowledge should be taken into account for assessing the sustainability of WMP harvesting.